ISOLASI DAN IDENTIFIKASI SENYAWA ANTIBAKTERI KULIT BATANG SALAM (Syzigium polyanthum (Wight) Walp.) - , Ni Luh Putu Vidya Paramita ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Leaf and stem bark of Syzygium polyanthum (Wight) Walp traditionally used for diarrhea. An acute diarrhea may be caused by a bacterial, viral or protozoan infection. The aim of this study is bioassay guided isolation of the antibacterial compound of S. polyanthum stem bark against four type bacterial that cause diarrhea. The antibacterial test using agar diffusion method. Elucidated of isolate using spectroscopy UV, IR, NMR, and LC-Mass. Ethanolic extracts of S. polyanthum stem bark can inhibit the growth of Shigella flexnerry ATCC 12022 at the loading dose of 250 Î¼g (6.6 mm), 500 Î¼g (9.3 mm), 750 Î¼g (8.9 mm) and 1000 Î¼g (10 mm), however it cannot inhibit the growth of the other three types of bacteria. Ethyl acetate fraction shows the most significant activity at the loading dose of 1000 Î¼g (10.6 mm) compared to ethanol fraction (8.6 mm) and the n-hexane fraction that does not show any inhibition. Fraction G (n-hexane: ethyl acetate(1:9 v /v)) and fraction H (ethyl acetate 100%) which obtained from ethyl acetate fraction can inhibit the growth S. flexnerry ATCC 12022 at the loading dose of 500 Î¼g at 8.6 mm and 8.98 mm. Isolate from fraction G and H cannot inhibit the growth S. flexnerry ATCC 12022. Identification of Isolate A1 which play the antibacterial activity of active fraction is terpenes derivate. Fraction G and H has antibacterial activity, but isolate from them cannot inhibit the growth S. flexnerry ATCC 12022. So all ingredients of the active fraction has synergistic effects.